Utilization of EPS Beats and Polypropylene Fiber in Controlled Low Strength Material - Minakshi Uchibagle; Dr. B Ram Rathan Lal (International Journal of Engineering and Management Research, 2021)
Controlled low-strength material (CLSM) is a self-levelling cementitious material. It is not concrete nor soil-cement, however, it possesses properties similar to both. CLSM is widely used as a replacement for soil-cement material in many geotechnical applications such as structural backfill, pipeline beddings, void fill, pavement bases and bridge approaches. This paper study potential possibility of polypropylene fiber in CLSM. Harden and fresh properties compressive strength , flowability and density for the proposed CLSM were investigated. This CLSM mix design with different percentage of polypropylene fiber and pond ash, cement and water. EPS beats and polypropylene add 0 %, 0.5%, 1.0% and 1.5% of total weight is added in CLSM MIx. Results show that the CLSM incorporating EPS beats and polypropylene satisfies compressive strength requirement as per the requirements of ACI committee 229. polypropylene decreases the flowability of CLSM mix and at the same tine by adding EPS beats the density of CLSM mix are reduce which become lightweight CLSM mix. from this it can conclude that polypropylene fibers is less effective in CLSM mix and EPS beats make CLSM mix lightweight which create lightweight CLSM mix applicable for filling application.